Immigration and Structural Change: Evidence from Post-War Germany - Sebastian Braun; Michael Kvasnicka (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Does immigration accelerate sectoral change towards high-productivity sectors? This paper uses the mass displacement of ethnic Germans from Eastern Europe to West Germany after World War II as a natural experiment to study this question. A simple two-sector specific factors model, in which moving costs prevent the marginal product of labor to be equalized across sectors, predicts that immigration boosts output per worker by expanding the high-productivity sector, but decreases output per worker within a sector. Using German district-level data from before and after the war, we find empirical support for these predictions.
Keywords: J61; F22; N34; 330